Implikasi Globalisasi dan Penegakan Hukum Progresif di Indonesia - Dharma Setiawan Pagaralam (Law Faculty of Universitas Bandar Lampung, 2011)
The Pancasila role in law national development at globalization era, globalization affects the economic, political and legal culture, making the relationship the countries is becoming one global village. The aspect of substance by the increasing adopted liberalism or neo-liberalism; and the cultural aspects affect the attitudes and behaviors that tend to be individualistic society. The Pancasila as an ideology and the basic state of Indonesia in the development of national law is a necessary âstaatsfundamentalnorm or rechtsidee